The Application of The Simple Evaluation Tilawah Method in Improving Memory Ability of the Qur'an - Mulianah, Baiq (Edumaspul: Jurnal Pendidikan, 2023)
This study aimed to find out the application of the Simple Evaluation Recitation Method in improving the ability to memorize the Al-Qur'an. The type of research used in this study is a qualitative research method with a qualitative descriptive study approach. Data was collected through library research (library research). The research results show that the Simple Evaluation Recitation Method is a method that familiarizes the memorizer of the Qur'an with an evaluation that anyone can do by combining recitations, murojaah and tahfidz. The indicators are 1) The teacher starts the teaching and learning process by praying together; 2) The teacher repeats the verses that have been taught before; 3) Santri listen; 4) Mental qin teacher of Al-Qur'an verses and followed by students; 5) Teachers and students read verses of the Koran together; 6) The teacher makes an assessment using the assessment form; 7) The teacher provides mixing of material regarding tajwid; 8) Santri are asked to take turns reciting verses from the Qur'an; 9) Santri smoothly and fluently memorizes the Al-Qur'an; 10) Accuracy of students in pronouncing makharijul letters; 11) The accuracy of the students using the tajwid law in reading the Qur'an; 12) The fluency of students in reading the Qur'an. In general, there are four evaluation types: a) Placement Evaluation; b) Formative Evaluation; and c) Summative Evaluation; d) Diagnostic Evaluation. Some indicators must be seen by people who will memorize the Al-Quran or Hafiz Al-Qur'an, namely 1) Fluency; 2) Tajweed; and 3) Letter Makhorijul.